Effects of ABT-4 on Seed Germination, Seeding Growth and Root Development of Jute Plant (CORCHORUS OLITORIUS L. JRO 632) - Dhakal, Min Raj; Rai, Shiva Kumar (Tribhuvan University Journal, 2011)
Available with full text. Key words: ABT-4; Seed Germination; Root Development Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 35-42 Uploaded date: 21 April, 2011